Clinical Evaluation of Postoperative Sensitivity in Class I Resin Composite Restorations - Cardoso, Renan Menezes; de Veras, Bruno Mendonça Lucena; Pedrosa, Marlus da Silva; da Silva, Claudio Heliomar Vicente (Brazilian Dental Science, 2020)
Objective: To evaluate the postoperative sensitivity in posterior restorations with different resin composites and adhesive systems as well as the influence of the depth and extent of the dental cavity. Material and Methods: A double-blind clinical trial was carried out with 80 class I restorations of 16 patients. The participants were divided into 4 groups according to the adhesive system + composite: F + P (Filtek P90™ + P90™); R + S (Rok™ + Stae™); P + A (P60™ + Adper SE PLUS™); E + X (Evolux™ + XPBond™ Adhesive). After 7, 15 and 30 days, the presence of postoperative sensitivity was evaluated and classified according to type and intensity. The data were submitted to Pearson's chi-square test, Fisher's exact teste, Student’s t-test and ANOVA. A significance level of 5% was used for all tests. Results: The presence of postoperative sensitivity was approximately 6% of the total sample. The sensitivity decreased with the evaluation time, with the smallest reduction occurring from the 7-day evaluation compared to the other evaluations. Conclusion: There was found no evidence of influence of the resin composite and adhesive type, depth and extension of the cavities for the presence of postoperative sensitivity.KeywordsDentistry; Dentin sensitivity; Adhesives; Composite resins.